First Robinsoniella peoriensis aortic cross homograft mycotic pseudoaneurysm: A case report and review of the literature. (April 2017) - Mertes, H.; Defourny, L.; Tré-Hardy, M.; Lhommel, R.; El Khoury, G.; Rodriguez-Villalobos, H.; Belkhir, L.
Abstract: Mycotic aortic aneurysm is a rare and challenging complication of aortic homografts caused by an infection and is associated with high morbidity and mortality. We report the first case of an aortic cross homograft mycotic pseudoaneurysm caused by Robinsoniella peoriensis in a 70-year-old man. Our patient underwent surgery for a recurrence of aortic cross mycotic pseudoaneurysm at the level of the aortic homograft he had had 7 years before. A clot-removal of the pseudoaneurysm was surgically carried out and the homograft was completely removed. Anaerobic culture from tissue samples yielded pure growth of a spore-forming Gram-positive rod, identified later as Robinsoniella peoriensis by 16S rRNA gene sequencing. The patient was then discharged with oral clindamycin according to the in vitro susceptibility testing. Identification of R . peoriensis might be challenging in clinical laboratories with no access to molecular methods.